Antibacterial activity evaluation of selected essential oils in liquid and vapor phase on respiratory tract pathogens - Kamilla Ács (BMC Complementary and Alternative Medicine, 2018)
Abstract Background The increasing number of multidrug-resistant bacteria and the fact of antibiotic resistance is leading to a continuous need for discovering alternative treatments against infections, e.g. in the case of respiratory tract diseases. Essential oils (EOs), because of their volatility, can easily reach both the upper and lower parts of the respiratory tract via inhalation. Therefore, the aim of the present study was the antibacterial evaluation of clove, cinnamon bark, eucalyptus, thyme, scots pine, peppermint, and citronella EOs against respiratory tract pathogens such as Streptococcus pneumoniae, S. mutans, S. pyogenes, Haemophilus influenzae, H. parainfluenzae, and Moraxella catarrhalis. Furthermore, we wanted to compare the antibacterial effect of these EOs in two different test systems to provide data for the development of an appropriate product formulation. Methods Minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) were determined with in vitro vapor phase test (VPT) and broth macrodilution test (BDT). The chemical and percentage compositions of the EOs were determined by GC-MS and GC-FID analysis. Results Among the EOs, thyme was the most effective against S. mutans (MIC: 0.04 mg/mL in BDT, but cinnamon bark and clove oils also presented high inhibition in liquid medium with MIC values of 0.06 mg/mL and 0.1 mg/mL against S. pneumoniae and S. pyogenes, respectively. M. catarrhalis was the most sensitive to thyme EO (MIC: 0.09 mg/mL). Cinnamon bark EO was the most effective against Haemophilus spp. (MIC: 0.06 mg/mL). In the VPT, cinnamon bark was the most effective oil against all investigated pathogens with MIC values in the range of 15.62–90 μl/L. Surprisingly, the eucalyptus and scots pine showed weak activity against the test bacteria in both test systems. Conclusions The EO of thyme, clove and cinnamon bark may provide promising antibacterial activity against respiratory tract pathogens either in liquid medium or in vapor phase. However, their effect is lower than that of the reference antibiotics. The combination of EOs and antibiotics may be beneficial in the alternative treatment of respiratory tract diseases. In vivo studies are necessary to calculate the effective dose of EOs in patients and determine their possible side effects and toxicity.